Mãe-bebê de risco : os desafios da interação inicial no contexto de internação hospitalar - Menegat, Danusa (2016)
Mother's affective bond with the baby is stablished from the first diade interactions as well as the quality of this relationship, which can be observed in several situations, from breastfeeding to playing. The puerperium, a period initiated soon after the baby bearing, may be a period tending to crisis, mainly when bearing a baby needing health care, what can cause some damage in this initial relationship. After the baby bearing this interaction may weaken when the mother bears a a premature baby, who needs to remain in the hospital environment. The knowledge about mother-baby interactions in the initial developing phases contributes to understand the human development process. The research intends to understand and characterize the interactional processes of risking mother-baby diade in the context of the hospitalization on the first days of life; characterize maternal behaviors present in the motherinfant interaction in hospital care and free interaction situations; identify and describe the factors that can interfere with the establishment of the initial interaction during the baby's hospital stay. This is a study qualitative, exploratory and descriptive approach. Semi-structures interview, field dairy and observation have been used as investigation techniques and data selection, in situations observed when feeding, bathing, diaper changing and free interacting. This study was conducted in two maternity, nursery and rooming-in, located in the state of São Paulo. The sample was composed of five babies, of both sexes, born between 34 and 37 weeks gestational age and their first-time mothers. The data analyses has been quanti-qualitative, by describing the mothers' behaviors, their occurence, and thematic content analysis as well. The data analysis allows the identification of seven categories: Event, pregnancy and childbirth: sensations, feelings and experienced changes; physical and behavioral characteristics of the baby; mother-infant initial interaction; hospital and staff: facilities and interference in the interaction; difficulties mothers; emotional support; concerns and expectations. The results show the complexity of maternal experience in hospital context of premature child, permeated by fear, insecurity and doubts arising from the baby's fragility. It was identified facilitating factors such as the presence of family members in the hospital, and complicating factors, such as performing breastfeeding and actively participate in the care of the baby. The bath was touted as the hardest care to be carried out, related to the newborn fragility and the mother of inexperience. It is concluded that the mothers have expected behaviors with their babies in the initial interaction, still in the hospital environment. In some contexts as well as in hospitalization the service dynamisc/routine and the professional attitudes/postures generate stress. New researches are supposed to be performed in order to spread the comprehension about caring actions which should be humanized and implemented to grant the positive future development of the mother-baby diade.